2016
DOI: 10.2166/wst.2016.580
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and antifungal susceptibility of opportunistic yeast pathogens from rivers

Abstract: Yeasts from water sources have been associated with diseases ranging from superficial mucosal infections to life threatening diseases. The aim of this study was to determine the water quality as well as diversity and antifungal susceptibility of yeasts from two rivers. Yeast levels and physico-chemical parameter data were analyzed by principal component analysis to determine correlations between physico-chemical data and yeast levels. Yeast morphotypes were identified by biochemical tests and 26S rRNA gene seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…TDS values were within TWQR for livestock farming (<1 000 mg/L) but above the recommended values for irrigation use (>40 mg/L). The high TDS values that were found in the NWP rivers by the current and by previous studies (Van Wyk et al, 2012;Monapathi et al, 2017) could have occurred as a result of dolomitic springs which are water sources for some of the river systems (Van Der Walt, 2002).…”
Section: Physico-chemical Parameters and Yeast Levelsmentioning
confidence: 61%
See 3 more Smart Citations
“…TDS values were within TWQR for livestock farming (<1 000 mg/L) but above the recommended values for irrigation use (>40 mg/L). The high TDS values that were found in the NWP rivers by the current and by previous studies (Van Wyk et al, 2012;Monapathi et al, 2017) could have occurred as a result of dolomitic springs which are water sources for some of the river systems (Van Der Walt, 2002).…”
Section: Physico-chemical Parameters and Yeast Levelsmentioning
confidence: 61%
“…The 26S rRNA gene fragments of the extracted DNA were amplified using the polymerase chain reaction (PCR) procedure as described by Monapathi et al (2017). Forward primers, NL1 (5-GCATATCAATAAGCGGAGGAAAAG-3) and reverse primers, NL4 (5-GGTCCGTGTTTCAAGACGG-3) (O'Donnell, 1993) were used.…”
Section: Amplification and Sequence Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, Zuza‐Alves et al reported a rate of fluconazole resistance as high as 43% in environmental C tropicalis from a Brazilian sand beach, with 24% of the isolates being multi‐azole resistant 52 . Similar observations were reported from soil samples in Taiwan, 53 and among C albicans isolates from environmental sources in Brazil, Japan and South Africa 54‐56 . Additionally, various levels of resistance to the medical antifungals fluconazole and flucytosine have been described in environmental Cryptococcus isolates 57,58 …”
Section: The Environmental Sphere: Is Our Environment An Underestimat...mentioning
confidence: 70%